Enhanced quality factors and force sensitivity by attaching magnetic beads to cantilevers for atomic force microscopy in liquid - Hoof, Sebastian; Gosvami, Nitya Nand; Hoogenboom, Bart (Journal of applied physics, 2012)
Dynamic-mode atomic force microscopy (AFM) in liquid remains complicated due to the strong viscous damping of the cantilever resonance. Here, we show that a high-quality resonance (Q>20) can be achieved in aqueous solution by attaching a microgram-bead at the end of the nanogram-cantilever. The resulting increase in cantilever mass causes the resonance frequency to drop significantly. However, the force sensitivity-as expressed via the minimum detectable force gradient-f is hardly affected, because of the enhanced quality factor. Through the enhancement of the quality factor, the attached bead also reduces the relative importance of noise in the deflection detector. It can thus yield an improved signal-to-noise ratio when this detector noise is significant. We describe and analyze these effects for a set-up that includes magnetic actuation of the cantilevers and that can be easily implemented in any AFM system that is compatible with an inverted optical microscope.
Gesehen am 30.08.2018